DENSITY OF THERMODYNAMIC EQUILIBRATED OF THE GRANITE’S MINERAL ASSOCIATIONS - SHABATURA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It is definite the dependence between density and thermodynamics parameters into equilibrated albite-anorthite-orthoclase associations of granites. Stability of position of density points in dimension pressure-temperature-H2O according the feldspars' eutectic is shown.